1989
DOI: 10.1002/lipi.19890910106
|View full text |Cite
|
Sign up to set email alerts
|

Sterinzusammensetzung und Steringehalt in 41 verschiedenen pflanzlichen und tierischen Fetten

Abstract: D a n ksagung Die eigenen Arbeiten wurden gefordert mit Hilfe von Forschungsmitteln des Bundesministers fur Forschung und Technologie (Forderkennzeichen 0319037 A8). Wir danken Frau C. Ohmstede und Herm E Bangert fiir technische Assistenz und Frau cand. chem. D. Grarnbergund Herm cand. chem. WRathje fiir ihre engagierte Mitarbeit. Eingegangen a m 27. Dezember 1988. Sterinzusa,mxnensemg und Steringehalt in 41 verschiedenen pflanzlichen und tierischen Fetten b n E p i e d e H o m b e r g undBirgitta B i e l e f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
7
6
0
Order By: Relevance
“…The total sterol content of the soybean oil samples analyzed ranged between 267.1 and 326.6 mg/100 g of oil. Those results are in accord with the literature (6,17,18,20). The distribution of the different phytosterols differed between the esterified and free sterol fraction.…”
Section: Respectivelysupporting
confidence: 93%
See 1 more Smart Citation
“…The total sterol content of the soybean oil samples analyzed ranged between 267.1 and 326.6 mg/100 g of oil. Those results are in accord with the literature (6,17,18,20). The distribution of the different phytosterols differed between the esterified and free sterol fraction.…”
Section: Respectivelysupporting
confidence: 93%
“…The highest phytosterol content was detected in corn and rapeseed oils, with a total phytosterol content ranging between 770 and 920 mg/100 g. The reported phytosterol distribution is in good accord with literature data (2,3,7,17,19,20).…”
Section: Respectivelysupporting
confidence: 86%
“…The total level given by the AOCS [17] is about 5800 mg/kg, while Crews et al found phytosterols in the range between 2580 and 11,250 mg/kg, with an average of 5710 mg/kg [7]. These values are in good agreement with an older publication [18]. Comparable to most of the other edible vegetable oils, b-sitosterol is the main phytosterol found in grape seed oil in the range from 67 to 70%.…”
Section: Phytosterol Compositionsupporting
confidence: 66%
“…A dietary plant sterol data base was formed combining analyzed data on the experimental fats and oils used in the diets of this study (van de Bovenkamp, unpublished) as well as analyzed data on fats used in Finland (Wester, unpublished) and data from other sources (Weichrauch and Gardner, 1978;Slover et al, 1980;Jonker et al, 1985;Souci et al, 1986;Homberg and Bielefeld, 1989;Edelman, 1993). About 300 foods in the national food composition database have a value for b-sitosterol, campesterol, and stigmasterol.…”
Section: Food Composition Datamentioning
confidence: 99%